Comparing User Perceptions of User Interface and User Experience in Learning Management Systems: A UEQ-Based Study Across Two Universities - Tri Setya Darmawan; Agung Fatwanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2026)
User perceptions toward software application interface and experience are important factors for the successful implementation of software systems. Therefore, this study was aiming to investigate these success factors by comparing user perceptions towards software application interface and experience when using software applications. This research used a inferential quantitative approach. The instrument used in this study was the UEQ (User Experience Questionnaire) formulated by the UEQ Team. The object of this study was two e-learning systems deployed at two state universities in Yogyakarta. Data on user perceptions toward software application interface and experience were collected twice. The collected data were then statistically analysed to obtain results for equivalence test, paired t-tests, Wilcoxon tests, statistical power, and Cohen's D values. Based on equivalence testing on the data gathered during the first and second collection stages, it was found that user perceptions toward software application interface and experience were equivalent and not different for most criteria and sub-criteria, except for the enjoyable, good, pleasing, and pleasant sub-criteria at University A and enjoyable, good, and motivating at University B. Meanwhile, based on the results of paired t-tests and Wilcoxon tests, it was found that user perceptions toward software application interface and experience were also equivalent and not different for most criteria and sub-criteria, except for the pleasing and good sub-criteria at University A, and the enjoyable and pleasing sub-criteria at University B. Therefore, it is concluded that there was generally no difference in user perceptions toward software application interface and experience when using those e-learning systems.